Panax Notoginseng Saponins Suppress Type 2 Porcine Reproductive and Respiratory Syndrome Virus Replication in vitro and Enhance the Immune Effect of the Live Vaccine JXA1-R in Piglets - Yi, Heyou; Yu, Zhiqing; Wang, Qiumei; Sun, Yankuo; Peng, Jie; Cai, Yu; Ma, Jun; Chen, Yongjie; Qin, Chenxiao; Cai, Mengkai; Ji, Chihai; Zhang, Guihong; et al. (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) suppresses the innate immune response in the host, reducing and delaying neutralizing antibody production against PRRSV infection and promoting viral infection. Here, we aimed to assess the potential of Panax notoginseng saponins (PNS) for improving the immune response exerted upon PRRSV-2-modified live virus (MLV) vaccine administration. Thirty piglets were randomly divided into six groups. Group 1 piglets were injected with medium 0 days post vaccination (dpv). Group 2 piglets were fed PNS 0-28 dpv. Group 3 and group 4 piglets were administered the JXA1-R vaccine 0 dpv. Group 4 piglets were also fed PNS 0-28 dpv. Group 1-4 piglets were challenged intranasally with the PRRSV JXA1 strain 28 dpv. Group 5 piglets were fed with PNS without challenge. Group 6 piglets served as controls. During the experiment, the samples were collected regularly for 49 days. Compared with group 1 piglets, group 3 piglets showed significantly reduced viremia and clinical scores, and significantly increased average daily gain (ADWG). Compared with group 3 piglets, group 4 piglets showed significantly improved neutralizing antibody titers, IFN-α and IFN-β mRNA expression, and significantly decreased viremia and viral load in the lungs and lymph nodes, but did not demonstrate any further improvement in PRRSV-specific antibody titer, rectal temperature, ADWG, or clinical scores. PNS upregulates neutralizing antibodies against PRRSV-2 and enhances the expression of IFN-α and IFN-β, which may reduce PRRSV viremia upon PRRSV-2 MLV vaccine administration. PNS may serve as an effective immunomodulator for boosting the immune defense against PRRSV.